Роль моделирования в формировании опыта самостоятельной работы студентов в процессе обучения в вузе - Михайличенко, Валентина Евдокимовна; Галущак, Ирина Владимировна; Гура, Татьяна Витальевна (Nowa Perspektywa Sp. z o.o, 2020)
В статье рассмотрена актуальная проблема использования педагогического моделирования для трансформации учебной деятельности в профессиональную в процессе обучения в вузе и для приобретения опыта самостоятельной работы студентами. Раскрыты теоретические основы понятий «педагогическая модель» и «педагогическое моделирование». Приведено содержание педагогического моделирования; его принципы, типы, этапы и способы, с помощью которых оно выстраивается в учебном процессе. Рассмотрена роль инновационных педагогических технологий для приобретения опыта самостоятельной работы студентов. Показана необходимость её активизации, чему способствуют моделирование профессиональной деятельности в аудиториях с помощью инновационных методов обучения и сотрудничество с производственными и социальными структурами и работодателями. Это требует совместной с работодателями разработки и внедрения практико-ориентированных учебных программ формирования новых образовательных конструктов, инвестирования студенческих проектов, разработки методических пособий по их использованию. Необходимо дальнейшее изучение данной актуальной проблемы, связанной с активизацией внедрения моделирования в учебный процесс.

The article deals with the theoretical fundamentals of modeling method and the ways of modeling method applying which professors should use in their innovative activity. Concept ‘pedagogical model’ and basic types of pedagogical models are considered. The content of pedagogical modeling and the fundamental principles, stages and tools of its forming are defined. A range of ‘model’ and ‘modeling’ concepts definitions which refer to the curtain investigation tasks are given. Theoretical investigation of problem analyzed allows to claim that pedagogical modeling is a creating of imaginary situations which require professional reactions and resolving of certain pedagogical problems. Different sides of the practical implementation of pedagogical modeling into the High school studying process that promote obtaining of the independent study of students are considered. The conflicts of theoretical and practical knowledge combining that can interfere this are revealed. Both displaying of industrial modeled activity in lecture halls with innovative educational methods and development of methodological tutorials of modeling processes usage will activate these processes. To summarize, developed technologies have two directions: the displaying of industrial modeled activity in lecture halls with innovative educational methods and the cooperation with industrial organizations and employers. It will require the union with the employers for the developing and implementation of practical oriented educational programs of forming new educational constructs, investment of students’ projects, generalization and sharing of the information about the innovative educational methods through the developing of methodological tutorials and the activating of these methods usage.
The role of modeling in the formation of students’ independent study experience during the high school studying process
Keywords: модель; педагогическое моделирование; обучение; активизация; самостоятельная робота; студент; образовательный процесс; model; pedagogical modeling; education; activation; independent study; student; educational process